Aldeinha: mas onde é mesmo a aldeia? - organização social e territorialidade - Souza, Sandra Cristina de (2010)
Terena group descended from the linguistic group / Txan, Tribe Guana initially divided into several sub-tribes, originating in the Chaco region, some of which crossed the Rio Paraguay in the century XVIII, being located by the missionaries on the banks of the Rio Miranda century XIX. Terena people inhabit the states of Mato Grosso, Mato Grosso and Sao Paulo, the first, the site currently where most of the villages are located in the municipalities of Aquidauana, Miranda, Paraguayans, Two Brothers Buriti, Dourados, Anastasios, Sidrolândia and Rock, with an approximate population of 23,000 individuals today. During the mid-nineteenth century and the beginning of this, many are the forms of involvement of Terena Indians and non-indigenous society. The non-indigenous institutions in most cases acted to integrate the Terena national society. Reflecting the pessimism with which indigenous peoples were seen until recently as the speech of an observer of the Terena community of the nineteenth century: There is much to be expected of the Indians. The various tribes of Guanas who inhabit the districts of Miranda and Albuquerque has the valuable services and living as they live among us, it is assumed that the new generations will be more restáveis and will soon merge with the masses of the population (Carvalho, 1979, p.43) We intend to analyze the process that produced the alternatives and strategies that allowed the survival of the Terena people and the continuity of their cultural reproduction. What was the history of this people, in particular, for the recovery of their territory, recovery of their language and ethnic affirmation? How did the incorporation of mixed race to the fostering of their population growth? How is intercultural between the religious (the figure of the transition koixomuneti to the priest / pastor), health (natural medicine to allopathic medicine, midwife to the hospital), language (oral culture to written culture - in school and the church)? Markedly institutions of "friction" between indigenous culture and non-indigenous culture are the church and school. The church in the period from the village (from the first decade of this century) to the present day presented in villages divided into several "appropriations" of Christianity: Catholicism, Protestantism and traditional Pentecostal. We want to better understand the reasons set out in the collective memory to "simulate" these changes in order to "know" the other (outsider), and thus circumvent the "integrationist" goal of the organ, the traditional, with two objectives: reducing discrimination and survive as ethnicity. Darci Ribeiro in the preface of the book "From the Indian Bugre" by Roberto Cardoso de Oliveira, recommends the group studies in advanced degree of integration for the contribution they can make in dealing with problems of survival of tribal people . Perhaps by noticing the nuance differentiated integration with the surrounding society that people were experiencing. For Carmen Junqueira talking about the unexpected resistance of indigenous peoples regarding the process of integration brought by the surrounding society, said: synchronic analysis, coupled with the selection of data that reinforce the vision of society as a stable structure prevented the backlog of these events, by sometimes ambiguous pointing to the change . Thus, students of Indian issue concluded "erroneously that indigenous societies were out of history, losing to the weaving of history . In this work we show that the company Terena is a multifaceted process that can not be properly called "integration", as their way of life is based on a tangle of traditions handed down through generations, which has the sense of community built on the daily lives of family relationships. So we can think of a compromise between the flat space (represented by the tradition) and the striated space (integration process promoted by the state), as proposed by Deleuze and Guattari. (1997, p.25)